Construction of MOOC Platforms in China - Zheng, Qinhua; Chen, Li; Burgos, Daniel (Lecture Notes in Educational Technology, 2020)
MOOC platforms in China have achieved quite some scale in China with its development since 2012. Built either by universities or enterprises on their own, or by regional coalitions or school–enterprise partnerships, MOOC platforms have provided vast and extensive opportunities for learners with different learning needs. Now we have nearly a hundred MOOC platforms offering courses on engineering, science, literature, management, economics, so on and so forth, for a range of users of different ages in primary and secondary education, higher education, vocational education, and adult education, which have significantly promoted the development of online education, equal access to education, cooperation between universities and relevant work in educational research.
Capítulo del libro "Zheng Q., Chen L., Burgos D. (2018). Lecture Notes in Educational Technology. Springer, Singapore"
Keywords: Scopus(2); WOS(2)